2022
DOI: 10.3389/fgene.2022.827538
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of chicken housekeeping genes using next-generation sequencing data

Abstract: Accurate normalization of the gene expression assays, using housekeeping genes (HKGs), is critically necessary. To do so, selection of a proper set of HKGs for a specific experiment is of great importance. Despite many studies, there is no consensus about the suitable set of HKGs for implementing in the quantitative real-time PCR analyses of chicken tissues. A limited number of HKGs have been widely used. However, wide utilization of a little number of HKGs for all tissues is challenging. The emergence of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Transcriptome analysis using technologies such as DNA microarrays, RNA-Seq, and other methods is in demand to evaluate gene expression ( Lovén et al , 2012 ; Hasanpur et al , 2022 ). However, the qPCR remains a valid and preferred tool to validate the results obtained by transcriptomic analyses ( Garrido et al , 2020 ; Hasanpur et al , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptome analysis using technologies such as DNA microarrays, RNA-Seq, and other methods is in demand to evaluate gene expression ( Lovén et al , 2012 ; Hasanpur et al , 2022 ). However, the qPCR remains a valid and preferred tool to validate the results obtained by transcriptomic analyses ( Garrido et al , 2020 ; Hasanpur et al , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis using technologies such as DNA microarrays, RNA-Seq, and other methods is in demand to evaluate gene expression ( Lovén et al , 2012 ; Hasanpur et al , 2022 ). However, the qPCR remains a valid and preferred tool to validate the results obtained by transcriptomic analyses ( Garrido et al , 2020 ; Hasanpur et al , 2022 ). Normalization strategies are needed to achieve accurate results, and reference genes as markers of stability is a common and effective method used for qPCR normalization in the relative quantification method ( Vandesompele et al , 2002 ; Samiullah et al , 2017 ; Garrido et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal reference genes are characterized by their consistent expression across various tissue types and cells, unaffected by external factors such as the environment, experimental conditions, or other variables. Nevertheless, the absence of a universally ideal reference gene applicable to all tissues necessitates caution ( Hasanpur et al, 2022 ; Mogilicherla et al, 2022 ), as certain commonly utilized reference genes, including glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ), beta-actin ( β-Actin ), exhibit unsuitability in specific tissues due to their inherent variability ( Glare et al, 2002 ; Barber et al, 2005 ; Lin and Redies, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a significant increase in scholarly investigations concerning reference genes in various tissues of domesticated animals ( Bonnet et al, 2013 ; Vorachek et al, 2013 ; Cieslak et al, 2015 ; Park et al, 2015 ; Faheem and Khaliq, 2019 ; Wang et al, 2022 ). Notably, in the case of chickens ( Gallus gallus ), several studies have successfully identified stable reference genes under different conditions ( Cedraz De Oliveira et al, 2017 ; Hassanpour et al, 2019 ; Rodríguez Hernández et al, 2021 ), and the evaluation of genes employed for gene expression analysis in major chicken organs has also been established ( Hasanpur et al, 2022 ). However, the absence of a dependable reference gene applicable to multiple tissues remains a challenge.…”
Section: Introductionmentioning
confidence: 99%